Hubungan Kausalitas Infrastruktur Transportasi Jalan dan Pertumbuhan Ekonomi Regional di Provinsi Jambi Periode 2013–2024 - Novia Magdalena Br. Tindaon; Zulgani; Etik Umiyati (PT. Hasba Edukasi Mandiri, 2026)
This study examines the causal relationship between road transportation infrastructure and regional economic growth in Jambi Province during 2013Q1–2024Q4. The analysis uses quarterly time-series data derived from Gross Regional Domestic Product at constant prices and the road-good-condition indicator, then applies the Augmented Dickey-Fuller test, optimal lag selection, VAR stability testing, Johansen cointegration, Granger causality, and a Vector Error Correction Model. The results indicate a one-way short-run causal pattern: economic growth Granger-causes road infrastructure, while road infrastructure does not Granger-cause economic growth. However, both variables are cointegrated, showing a long-run equilibrium relationship. The findings suggest that improvements in road quality in Jambi tend to follow expanding economic activity and fiscal capacity, whereas the economic benefits of road development are more visible in the long term than in quarterly movements.